2018
DOI: 10.1101/410373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influenza A Virus Ribonucleoproteins Form Liquid Organelles at Endoplasmic Reticulum Exit Sites

Abstract: 18Influenza A virus has an eight-partite RNA genome that during viral assembly forms a 19 supramolecular complex containing one copy of each RNA. Genome assembly is a selective 20 process driven by RNA-RNA interactions and is thought to lead to discrete punctate structures 21 scattered through the cytosol. Here, we show that contrary to the accepted view, formation of 22 these structures is not dependent on RNA-RNA interactions among distinct viral 23 ribonucleoproteins (vRNPs), as they assemble in cells expre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 74 publications
(148 reference statements)
2
17
0
Order By: Relevance
“…We and others reported previously that membraneless phase-separated condensates of GFP-MxA in the cytoplasm, or IL-6-induced cytoplasmic and nuclear GFP-STAT3 condensates, or influenza A virus (FLUAV) maturation structures in the cytoplasm were rapidly disassembled (within 1-3 minutes) in cells swollen following exposure to hypotonic buffer (9,21,27,49). We further showed that a return of such cells to isotonic buffer caused rapid reassembly of MxA but in new structures different from the original ones (9,27,49).…”
Section: Disassembly Of Gfp-mx1 Nuclear Bodies By Hypotonicity and Rementioning
confidence: 96%
See 1 more Smart Citation
“…We and others reported previously that membraneless phase-separated condensates of GFP-MxA in the cytoplasm, or IL-6-induced cytoplasmic and nuclear GFP-STAT3 condensates, or influenza A virus (FLUAV) maturation structures in the cytoplasm were rapidly disassembled (within 1-3 minutes) in cells swollen following exposure to hypotonic buffer (9,21,27,49). We further showed that a return of such cells to isotonic buffer caused rapid reassembly of MxA but in new structures different from the original ones (9,27,49).…”
Section: Disassembly Of Gfp-mx1 Nuclear Bodies By Hypotonicity and Rementioning
confidence: 96%
“…In parallel with these insights, it has now been recognized that replication and maturation of negative-strand RNA viruses [e.g. vesicular stomatitis (VSV), rabies (as in Negri bodies), Ebola and measles viruses] occurs in cytoplasmic phase-separated condensates typically involving the viral nucleocapsid (N) protein with or without additional viral proteins (15)(16)(17)(18)(19)(20)(21). Even the replication of a DNA virus such as Epstein-Barr virus involves phase-separated nuclear bodies (22).…”
Section: Introductionmentioning
confidence: 99%
“…In this latter scenario, Rab11-vesicles would be the final transporters of vRNPs to the plasma membrane, conflicting with the lack of Rab11 in virions and at the plasma membrane, but consistent with a modest role for microtubules during infection. Supporting data for an involvement of the ER includes a preprint manuscript showing that viral inclusions form in the vicinity of ER exit sites (ERES) in a way that is dependent on continuous cycles between the ER and the Golgi (Alenquer et al, 2018).…”
Section: Functional Relevance Of Rab11 During Iav Infectionmentioning
confidence: 99%
“…Additionally, viral inclusions were shown to be established in cells expressing one single vRNP indicating that the formation of these structures precedes (and is not contingent on) the establishment of RNA–RNA interactions. Furthermore, viral inclusions were shown to have liquid properties segregating from the cytosol without a delimiting membrane, being able to exchange material dynamically, and deform easily as well as to adapt fast to changes in the cellular environment (Alenquer et al, 2018). Therefore, given the liquid properties of viral inclusions and although it is possible that vesicles in these structures collide to establish vRNP intersegment interactions, other unidentified processes could also take place.…”
Section: Functional Relevance Of Rab11 During Iav Infectionmentioning
confidence: 99%
See 1 more Smart Citation